Evolutionary resilience and complex lagoon systems. (10th August 2016) - Davoudi, Simin; Zaucha, Jacek; Brooks, Elizabeth
ABSTRACT: The present study applies an evolutionary resilience framework to complex socioecological systems in the coastal regions in Europe with a particular focus on lagoons. Despite their variations, lagoons share common challenges in achieving effective and sustainable ways of governing and managing economic, social, and environmental uncertainties. Our aim is to demonstrate that building resilience involves planning not only for recovery from shocks but also for cultivating preparedness and seeking potential transformative opportunities that emerge from change. The framework consists of 4 dimensions: persistence, adaptability, transformability, and preparedness. To illustrate how this 4‐dimensional framework can be applied to the specific context of lagoons, we draw on examples of good and poor practices from the 10 lagoons studied as part of the ARCH project. Integr Environ Assess Manag 2016;12:711–718. © 2016 SETAC. Key Points: Lagoons (estuaries and fjords) are dynamic and complex socioecological systems shaped by natural processes in interaction with social and economic pressures. The ARCH project aimed to integrate relevant scientific disciplines with policy to inform a stakeholder engagement process to further sustainable lagoon management across 10 European lagoon systems. This article goes beyond sustainable management to explore the idea of resilience as this relates to examples from the ARCH project lagoons, explaining 3 types of resilience, the latter of which, evolutionary resilience, is argued to be the most appropriate for complex lagoon systems. Positive and negative examples from the ARCH project lagoons illustrate the 4 components of evolutionary resilience, contrasting the tendency to seek to return to "normal" with more dynamic and transformational approaches.